Optimization of Organic Rice Production using Linear Programming Analysis in Lampung Province - Sri Handayani (AIBPM Publisher, 2022)
Organic rice cultivation in Lampung Province is less developed because most farmers do a double cropping system that is on adjacent land to plant various types of plants to anticipate organic lower price. The problem faced by farmers is the management of cropping system, especially in maximizing revenue gains from managing resources. During this time farmers has not been able to obtain an ideal profit, only in the break-even stage between business income and expenditure. This study aims to: (1) determine the optimization model of production and maximum profit of farming, and (2) determine the optimal allocation of production resources. The research was conducted in Pringsewu and Lampung Selatan Districts. The respondents are 20 organic rice farmers. The research method used is a quantitative method using Linear Programing analysis method using POM-QM for windows 3.0 helper software. The result shows that Linear Function for Z max objective = 30,573X1 + 16,906X2 + 1,500X3 where X1, X2, and X3 are organic rice, non-organic rice, and soybean. The optimal production of farming is only producing organic rice with planting area of 19.2713 hectares and the maximum profit obtained is Rp.589,181,300,-. Optimization model of organic rice farming production is Max Z = 30573X1. The use resources of land, labor and seeds is not optimal yet or unutilized while the availability is at the farmers' level of excess, so that under optimal conditions land use, labor and seeds need to be added from the existing stock. The allocation of used capital resources shows that its use has been optimal and if the farmers increase the capital utilization by 1 unit, it will increase the business profit by Rp 2.282,-Â Â Keywords: - Organic Rice, Production Optimization, Linear Programming